The secret life of John le Carré - Sisman, Adam (Harper, an imprint of HarperCollinsPublishers, 2023)
Secrecy came naturally to John le Carre, and there were some secrets that he fought fiercely to keep. Adam Sisman's definitive biography, published in 2015, provided a revealing portrait of this fascinating man; yet some aspects of his subject remained hidden. Nowhere was this more so than in his private life. Apparently content in his marriage, the novelist conducted a string of love affairs over five decades. To these relationships he brought much of the tradecraft that he had learned as a spy - cover stories, cut-outs and dead letter boxes. These clandestine operations brought an element of danger to his life, but they also meant deceiving those closest to him. Small wonder that betrayal became a running theme in his work. In trying to manage his biography, the novelist engaged in a succession of skirmishes with his biographer. While he could control what Sisman wrote about him in his lifetime, he accepted that the truth would eventually become known. Following his death in 2020, what had been withheld can now be revealed. The Secret Life of John le Carre reveals a hitherto-hidden perspective on the life and work of the spy-turned-author and a fascinating meditation on the complex relationship between biographer and subject. 'Now that he is dead,' Sisman writes, 'we can know him better.'
Originally published: London : Profile Books, 2023
A supplement to Sisman's biography of Le Carré (published in 2015) that focuses on material his subject did not want to see published during his lifetime
Keywords: Le Carré, John -- 1931-2020; Le Carré, John / 1931-2020; Le Carré, John / 1931-2020 / Relations with women; Le Carré, John / 1931-2020 / Friends and associates; Novelists, English / 20th century / Biography; Novelists, English / 21st century / Biography; Intelligence officers / England / Biography; Romanciers anglais / 20e siècle / Biographies; Romanciers anglais / 21e siècle / Biographies; Officiers de renseignements / Angleterre / Biographies; POLITICAL SCIENCE / Intelligence & Espionage; Friendship; Intelligence officers; Novelists, English; Relations with women; England; 1900-2099; Biographies; Biografie